Cross-boundary subsidy cascades from oil palm degrade distant tropical forests - Matthew Scott Luskin (Nature Portfolio, 2017)
The expansion of agriculture and rangelands can cause ecological spillover effects across cultivated-natural ecosystem boundaries. Here, Luskin et al. show irruptions of oil palm-subsidized wild boar alter the abundance and diversity of understory trees >1 km into a primary forest reserve in Malaysia.